Characteristics of hemp fibre reinforced foam concretes with fly ash and Taguchi optimization - Kaplan, Gökhan; Tek, Murat; Bodur, Burak; Gençel, Osman; Bayraktar, Oğuzhan Yavuz; Benli̇, Ahmet; Martinez-Barrera, Gonzalo; Brostow, Witold (Elsevier BV, 2021)
Abstract This study presents investigation on microstructural, mechanical, durability and thermal characteristics of hemp fibers (HFs) reinforced foam concrete with fly ash (FA) and Taguchi optimization approach. Three series of foam concretes mixtures were produced with foam contents of 50, 75 and 100 kg/m3. There is a reference mixture without HFs and FA. Thus, mixtures contain FA as cement replacement at the concentrations of 0%, 10%, 20%, 30%, 40% and 50%. HFs with varying fiber length were introduced into mixes at concentrations of 0.75%, 1.5% and 3% by weight of cement. Slump test was done to see workability. Compression and flexural properties were determined at 7, 28 and 91 days. Durability was investigated by high temperature, freeze–thaw and sulphate exposures. Thermal conductivity, drying shrinkage, porosity, water absorption and dry unit weight properties of foam concretes were also investigated. Experimental results were analyzed using Taguchi optimization approach. Addition of HFs provides very large compressive and flexural strength enhancements. FA addition reduces the drying shrinkage and thermal conductivity while it increases the high temperature resistance of foam concretes.
Keywords: Physico-Mechanical Properties; Durability Properties; Foam Concrete; Hemp Fibers; General Materials Science; Fly Ash; Taguchi Optimization